Self-healing properties of steel slag asphalt mixture based on experimental characterization and 3D reconstruction - Liu, Jianan; Wang, Zhenjun; Jing, Haosen; Zhang, Tonghuan; Wang, Xiaofeng; Zhou, Xiaowei; Xu, Xu (Materials & design, 2023)
[Display omitted] •Steel slag as a microwave absorber can significantly improve the microwave sensitivity of steel slag asphalt mixture.•The self-healing rate of steel slag asphalt mixture can be increased by more than 30% under microwave heating.•The damage and healing state can affect the internal void size, shape, and connectivity characteristics of asphalt mixture.•Fissures and connected voids are proposed to quantitatively evaluate the damage and healing of steel slag asphalt mixture. Asphalt pavement is susceptible to cracking which affects its service life. And self-healing technology helps to heal micro-cracks in mixture at an early stage, but its mechanism of action at the mesoscale is still unclear. Therefore, the composition of steel slag asphalt mixture (SSAM) was designed, microwave heating performance, healing performance and road performance of SSAM were investigated by laboratory experiments. Finally, the SSAM was scanned using X-ray CT for 3D reconstruction and quantitative analyses. The results show that steel slag has obvious magnetic loss characteristics; the surface temperature of SSAM designed by composition is higher under microwave heating to obtain a better healing rate, and the road performance of SSAM meets the specification requirements. The damage-healing process mainly affects voids in SSAM, and microwave healing can reduce the fractal dimension of voids to reduce the proportion of fissures; from the healing index based on voids, self-healing can reduce the average coordination number and throat number of connected voids, thereby improving the performance of SSAM by reducing permeability. The self-healing performance of SSAM is improved through its compositional design; the mesoscopic model based on void characteristics helps to refine the theory of self-healing of asphalt mixtures under microwave heating.